2020
DOI: 10.23937/2378-3656/1410298
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Use and Depression: Comparison of Natural and Synthetic Cannabinoids

Abstract: Purpose: Patients who predominantly used marijuana (natural cannabis) and patients who predominantly used synthetic cannabinoids in their history were evaluated as two separate groups in our study which aimed to compare the sociodemographic characteristics and depressive symptoms of these two groups. Method: The sample of our study consisted of those patients who referred to the Polyclinic of Psychiatry at Ardahan State Hospital and were diagnosed with substance addiction. 30 polyclinic patients who defined pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Authors of the study additionally advise caution in the long-term cannabis use, due to alternations in the endocannabinoid system, which paradoxically may increase patients’ susceptibility to depression and reverse the positive effects of the therapy [ 62 ]. Moreover, a number of participants enrolled in other trials experienced negative results of the treatment, such as paranoia, irritation, dysphoria, demotivation or depression [ 11 , 53 , 63 , 64 , 65 , 66 ]. Additionally, the abuse risk assessment is necessary, similarly to the case of using opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of the study additionally advise caution in the long-term cannabis use, due to alternations in the endocannabinoid system, which paradoxically may increase patients’ susceptibility to depression and reverse the positive effects of the therapy [ 62 ]. Moreover, a number of participants enrolled in other trials experienced negative results of the treatment, such as paranoia, irritation, dysphoria, demotivation or depression [ 11 , 53 , 63 , 64 , 65 , 66 ]. Additionally, the abuse risk assessment is necessary, similarly to the case of using opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Many synthetic cannabinoids contain added substances (including benzodiazepines and O-desmethyltramadol) to increase their psychoactive effect. This study measured depression using the Beck Depression Inventory and found that, while depression scores were high in both groups, there was a statistically significant increase in depressive symptoms in participants using synthetic cannabinoids compared to those using marijuana [123] .…”
Section: Drug Interactionsmentioning
confidence: 95%
“…As mentioned previously, there are numerous preclinical and clinical studies pointing out that cannabis/THC and SCs use significantly contributes to the development of depression [3,6,8,[50][51][52][53]. In fact, a recent study showed that SC users displayed a higher Beck Depression Inventory score [54] compared to natural cannabis users, with similar socio-demographic characteristics [51].…”
Section: The Endocannabinoid Systemmentioning
confidence: 96%
“…As mentioned previously, there are numerous preclinical and clinical studies pointing out that cannabis/THC and SCs use significantly contributes to the development of depression [ 3 , 6 , 8 , 50 , 51 , 52 , 53 ]. In fact, a recent study showed that SC users displayed a higher Beck Depression Inventory score [ 54 ] compared to natural cannabis users, with similar socio-demographic characteristics [ 51 ]. Another study pointed out a similar outcome, where SC use was associated with increased mental health symptomatology—including depression—compared to natural cannabinoid use [ 10 ].…”
Section: Introductionmentioning
confidence: 99%